Barriers and enablers of vigorous intermittent lifestyle physical activity (VILPA) in physically inactive adults: a focus group study - C. Thøgersen-Ntoumani; M. Kritz; A. Grunseit; J. Chau; M. Ahmadi; A. Holtermann; A. Koster; C. Tudor-Locke; N. Johnson; C. Sherrington; S. Paudel; C. Maher; et al. (BMC, 2023)
Abstract Background Vigorous Intermittent Lifestyle Physical Activity (VILPA) refers to brief bouts of vigorous intensity physical activity performed as part of daily living. VILPA has been proposed as a novel concept to expand physical activity options among the least active. As a nascent area of research, factors which impede or encourage VILPA in physically inactive adults are yet to be explored. Such information is pertinent in the design of future interventions. We examined the barriers and enablers of VILPA among physically inactive adults using the Capability, Opportunity, Motivation, Behavior (COM-B) model as a conceptual framework. Methods We recruited a sample of self-identified physically inactive middle-aged and older adults (N = 78) based in Australia to take part in 19 online focus groups across three age groups: young-middle (age 35-44), middle (age 45-59) and old (age 60-76). We analyzed interviews using a critical realist approach to thematic analysis. Identified barriers and enablers were subsequently mapped onto the COM-B model components. Results The data generated 6 barriers and 10 enablers of VILPA that corresponded to COM-B concepts. Barriers included physical limitations (physical capability), perceptions of aging, need for knowledge (psychological capability), environmental constraints (physical opportunity), perceptions of effort and energy, and fear (automatic motivation). Enablers included convenience, reframing physical activity as purposeful movement, use of prompts and reminders (physical opportunity), normalization of taking the active option, gamification (social opportunity), sense of achievement, health improvements, personally salient rewards (reflective motivation), identity fit, and changing from effortful deliberation to habitual action (automatic motivation). Conclusion The barriers and enablers of VILPA span capability, opportunity, and motivation beliefs. Promoting the time-efficient nature and simplicity of VILPA requiring no equipment or special gym sessions, the use of prompts and reminders at opportune times, and habit formation strategies could capitalize on the enablers. Addressing the suitability of the small bouts, the development of specific guidelines, addressing safety concerns, and explicating the potential benefits of, and opportunities to do, VILPA could ameliorate some of the barriers identified. Future VILPA interventions may require limited age customization, speaking to the potential for such interventions to be delivered at scale.